Changes in Membrane Cholesterol Differentially Influence Preferential and Non-preferential Signaling of the M1 and M3 Muscarinic Acetylcholine Receptors - Michal, Pavel; El-Fakahany, Esam E; Doležal, Vladimír (Neurochemical research, 2015)
We have found earlier that changes in membrane cholesterol content have distinct impact on signaling via the M1, M2, or M3 receptors expressed in CHO cells (CHO-M1 through CHO-M3). Now we investigated whether gradual changes in membrane cholesterol exerts differential effects on coupling of the M1 and M3 muscarinic receptors to preferential signaling pathways through Gq/11 and non-preferential Gs G-proteins signaling. Changes in membrane cholesterol resulted in only marginal alterations of antagonist and agonist affinity of the M1 and M3 receptors, and did not influence precoupling of either subtype. Changes in membrane cholesterol did not influence parameters of carbachol-stimulated GTP-γ(35)S binding in CHO-M1 membranes while reduction as well as augmentation of membrane cholesterol lowered the efficacy but increased the potency of carbachol in CHO-M3 membranes. Gradual increase or decrease in membrane cholesterol concentration dependently attenuated agonist-induced inositolphosphates release while only cholesterol depletion increased basal values in both cell lines. Similarly, membrane cholesterol manipulation modified basal and agonist-stimulated cAMP synthesis via Gs in the same way in both cell lines. These results demonstrate that changes in membrane cholesterol concentration differentially impact preferential and non-preferential M1 and M3 receptor signaling. They point to the activated G-protein/effector protein interaction as the main site of action in alterations of M1 receptor-mediated stimulation of second messenger pathways. On the other hand, modifications in agonist-stimulated GTP-γ(35)S binding in CHO-M3 membranes indicate that in this case changes in ligand-activated receptor/G-protein interaction may also play a role.
Keywords: cAMP synthesis; Animals; systémy druhého messengeru; Muscarinic receptors; Carbachol; cholesterol; receptor muskarinový M3; Second Messenger Systems; CHO buňky; Receptor, Muscarinic M3; G-Proteins; proteiny vázající GTP; lidé; karbachol; Receptor, Muscarinic M1; GTP-Binding Proteins; signální transdukce; Signal transduction; receptor muskarinový M1; Signal Transduction; Agonist binding; Cricetulus; Cholesterol; zvířata; CHO Cells; Humans